2012
DOI: 10.1021/jm300862u
|View full text |Cite
|
Sign up to set email alerts
|

Noncyclam Tetraamines Inhibit CXC Chemokine Receptor Type 4 and Target Glioma-Initiating Cells

Abstract: The three stereoisomers of the noncyclam compound 1 (1(R,R), 1(S,S), and the meso form 1(S,R)) and their corresponding tetrahydrochlorides 11 were prepared from (S)- and (R)-2-methylpiperidine. We have evaluated their inhibitory activity on the CXC chemokine receptor type 4 (CXCR4), toxicity properties, and assessment of their effect on glioma initiating cells (GICs) in comparison with the prototype compound AMD3100. The IC(50) values determined on human recombinant (CHO) cells showed very similar inhibitory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…ICT5040, compound 1 , also reduces CXCL12-induced proliferation of U87-glioma cells in a concentration dependent manner (Figure 14) consistent with the involvement of chemotactic axes in glioma proliferation[64,65]. We first showed that this receptor is expressed on the human glioma U87-MG cells (see file S2), and that the cell proliferation rates increase in response to CXCL12, the ligand for CXCR4 (Figure 14).…”
Section: Resultssupporting
confidence: 65%
“…ICT5040, compound 1 , also reduces CXCL12-induced proliferation of U87-glioma cells in a concentration dependent manner (Figure 14) consistent with the involvement of chemotactic axes in glioma proliferation[64,65]. We first showed that this receptor is expressed on the human glioma U87-MG cells (see file S2), and that the cell proliferation rates increase in response to CXCL12, the ligand for CXCR4 (Figure 14).…”
Section: Resultssupporting
confidence: 65%
“…11 More recently, we have synthesized three stereoisomers of compound 5 (5(R,R), 5(S,S), and the meso form 5(S,R)) and evaluated their effect on glioma initiating cells (GICs) in comparison with the prototype compound AMD3100. 14 Through our research and previous ones, a paradigm has been widely accepted: to use the p-phenylene moiety as the central core for the connection of nitrogen heterocycles linked to two nitrogen atoms on both sides of such a core. This paradigm, the presence of a single carbon atom between the central phenyl ring and the first nitrogen of the side chain, comes from the study of Bridger et al 15 who showed that, in the case of analogues 6 (Fig.…”
mentioning
confidence: 79%
“…3). The corresponding synthetic itineraries (Scheme 1) use 1,4-benzenediacetic acid (9) and 2-(4-(bromomethyl)phenyl)acetic (14) acid, respectively, and a library of amines of the general structure 12{x} as starting materials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations